THE IMPACT OF INFORMATION QUALITY ON THE DECISION-MAKING PROCESS IN A METALLURGICAL COMPANY: a case study using the flow chart and Pareto diagram - Maturo, Guilherme Ramalli; Carleto, Nivaldo (Revista Interface Tecnológica, 2020)
This article aims to show that within organizations, decision making is based on incomplete, fictitious data and to measure how much information is generated with this data. For this, a case study was carried out at Soberano Indústria de Máquinas e Equipamentos during thirty days in the Production Planning and Control and operational sectors of the company, so that it was possible to see if everything that was planned was executed and these same executions returned. For Production Planning and Control through notes. From the delivery of the notes, the analysis and manipulation of them were made through the Pareto Diagram and the process and those responsible for ensuring the generation and manipulation of the data to be transformed into information used by the company’s tactical / strategic management using the flowchart. The results obtained in this work prove the theories studied and mentioned, in which decision making is based on incomplete, inconsistent or even fictitious information, and it is possible to determine at what stage of the process there was an incomplete generation. It was concluded that most of the problem was present in filling out the notes. To remedy the problems found, training of operators was proposed to assist them in filling out the notes and expose them to the importance of the appointment for the future of the organization.